2003
DOI: 10.1364/oe.11.002225
|View full text |Cite
|
Sign up to set email alerts
|

Solid microstructured optical fiber

Abstract: An all-solid microstructured fiber based on two thermallymatched silicate glasses with a high index contrast has been fabricated for the first time. The microstructured cladding was shown to be essentially unchanged during fiber drawing. Fiber attenuation was measured as 5dB/m at 1.55µm by the cutback method. High nonlinearity 230 W -1 km -1 has been predicted and experimentally demonstrated in this fiber at 1.55µm. In addition, modeling predicts that near-zero dispersion can be achieved between 1.5-1.6µm in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 20 publications
2
54
0
Order By: Relevance
“…Observe that the resulting core and rings are highly circular and concentric. By examining SEMs for fibers with ODs ranging from 825 m to 135 m we were able to demonstrate that the microstructure geometry of this high-index-core 1D MOF is dimensionindependent as expected and consistent with previous observations made in 2D-structured SOlid HOle (SOHO) fibers [23]. This is an important advantage of solid MOF relative to air-filled holey fiber since it allows the stable and repeatable definition of transverse structure that is essential for achieving optical fibers with pre-determined optical characteristics.…”
Section: Fiber Fabricationsupporting
confidence: 87%
See 1 more Smart Citation
“…Observe that the resulting core and rings are highly circular and concentric. By examining SEMs for fibers with ODs ranging from 825 m to 135 m we were able to demonstrate that the microstructure geometry of this high-index-core 1D MOF is dimensionindependent as expected and consistent with previous observations made in 2D-structured SOlid HOle (SOHO) fibers [23]. This is an important advantage of solid MOF relative to air-filled holey fiber since it allows the stable and repeatable definition of transverse structure that is essential for achieving optical fibers with pre-determined optical characteristics.…”
Section: Fiber Fabricationsupporting
confidence: 87%
“…Whilst HFs are typically pure air glass structures it is worth noting that MF concepts can also be applied to solid fibers made from two glasses with substantially different refractive indices, provided of course that these glasses are adequately matched in terms of their thermal and mechanical properties [23]. This opens up new fabrication possibilities and provides significant advantages for certain fiber types -not least in the sense that the fiber geometry is defined at the preform fabrication stage and that only the structure scale is defined at the draw stage.…”
Section: Fiber Fabricationmentioning
confidence: 99%
“…Moreover, control of the fiber parameters during the drawing process is simpler and obtaining fiber parameters similar to the designed ones is straightforward (Buczynski et al 2012a, b). The development of ASPCFs has been reported by several groups (Feng et al 2003;Luan et al 2004;Buczynski et al 2012a, b) and successfully reported for supercontinuum generation (Kibler et al 2009;Wang et al 2012;Stepniewski et al 2014). Introduction of subwavelength inclusions in the core enables an additional degree of freedom in shaping of dispersion profile, while maintaining a constant value of effective mode area (Buczynski et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…A cross−section of a typical PCF (whose first prototype has been demonstrated by the group of P. Russell in 1996 [2]) consists of two main sec− tions -namely, the circular core and the annular cladding. The latter acts as a photonic lattice (designed on the same scale as a wavelength) and is formed by the periodic matrix (typically square or triangular) of microscopic air−holes or micro−rods distributed in a solid material (e.g., in pure silica [2][3], non−silica, high−index/multi−component glasses [4][5][6], silver−halide crystalline materials [7] or polymers [8][9]). The core region can be either made of solid materials (as in conventional fibres) [1][2][3][4][5]7,8], or remain hollow [1,3,6,9] (as it is also in the structure presented here).…”
Section: Introductionmentioning
confidence: 99%